Hydroxychloroquine for Early Treatment of Adults With Mild Coronavirus Disease 2019: A Randomized, Controlled Trial. (16th July 2020) - Mitjà, Oriol; Corbacho-Monné, Marc; Ubals, Maria; Tebé, Cristian; Peñafiel, Judith; Tobias, Aurelio; Ballana, Ester; Alemany, Andrea; Riera-Martí, Núria; Pérez, Carla A; Suñer, Clara; Laporte, Pep; et al.
Abstract: Background: No effective treatments for coronavirus disease 2019 (COVID-19) exist. We aimed to determine whether early treatment with hydroxychloroquine (HCQ) would be efficacious for outpatients with COVID-19. Methods: Multicenter open-label, randomized, controlled trial conducted in Catalonia, Spain, between 17 March and 26 May 2020. Patients recently diagnosed with <5-day of symptom onset were assigned to receive HCQ (800 mg on day 1 followed by 400 mg once daily for 6 days) or usual care. Outcomes were reduction of viral load in nasopharyngeal swabs up to 7 days after treatment start, disease progression up to 28 days, and time to complete resolution of symptoms. Adverse events were assessed up to 28 days. Results: A total of 293 patients were eligible for intention-to-treat analysis: 157 in the control arm and 136 in the intervention arm. The mean age was 41.6 years (SD, 12.6), mean viral load at baseline was 7.90 log10 copies/mL (SD, 1.82), and median time from symptom onset to randomization was 3 days. No differences were found in the mean reduction of viral load at day 3 (−1.41 vs −1.41 log10 copies/mL in the control and intervention arm, respectively) or at day 7 (−3.37 vs −3.44). Treatment did not reduce risk of hospitalization (7.1% control vs 5.9% intervention) nor shorten the time to complete resolution of symptoms (12 days, control vs 10 days, intervention). No relevant adverse events were reported. Conclusions: In patients with mild COVID-19, no benefit was observed with HCQ beyond the usual care. Abstract : Compared with usual care, early treatment with HCQ failed to reduce the viral load in nasopharyngeal swabs after 3 and 7 days of treatment and shorten the time to resolve symptoms in adults with mild coronavirus disease 2019.